1937
DOI: 10.1017/s0025315400011899
|View full text |Cite
|
Sign up to set email alerts
|

Note on Selective Feeding by Calanus

Abstract: The rates at which Calanus finmarchicus eat both carmine particles and the diatom Nitzschia closterium have been investigated by Fuller &Clarke (1936) and Fuller (1937). They found that the number of Nitzschia or of carmine particles, eaten by a Calanus in unit time, was proportional to the concentration of Nitzschia or of particles in the water. Lucas (1936) also found that Neomysis and Eurytemora ate Nitzschia at rates which were roughly proportional to the concentration of diatoms in the water over fairly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0
1

Year Published

1961
1961
2005
2005

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 5 publications
4
59
0
1
Order By: Relevance
“…Yet the grazing rate computed for CaZanus in Table I was in one instance 70% that of the mysids and never as low as 10%. Grazing rates for CaZanus from 70 ml to over 200 ml/day have been reported in the literature (Gauld 1951;Harvey 1937). Raymont and Krishnaswamy ( 1960) found that N. integer was cannibalistic in laboratory culture.…”
Section: Discussionmentioning
confidence: 99%
“…Yet the grazing rate computed for CaZanus in Table I was in one instance 70% that of the mysids and never as low as 10%. Grazing rates for CaZanus from 70 ml to over 200 ml/day have been reported in the literature (Gauld 1951;Harvey 1937). Raymont and Krishnaswamy ( 1960) found that N. integer was cannibalistic in laboratory culture.…”
Section: Discussionmentioning
confidence: 99%
“…Both the dependent variables and animal size were transformed to their decimal logarithms because such transformations usually linearize interspecific body size relations (Brody 1945;Bonner 1965;Peters 1983 Ambler and Frost 1974;Anraku and Omori 1963;Baudouin and Ravera 1972;Bogdan and McNaught 1975;Comita 1968;Comita and Schindler 1963;Conover 1959;Durbin and Durbin 1978;Harvey 1937;Hebert 1978;Heinle 1966;Kryutchkowa and Rybak 197 1;Lemcke and Lampert 1975;McMahon and Rigler 1965;Marshall and Orr 1955;Moshiri et al 1969;Nival et al 1974;Omori 1970;Rakusa-Suszczewski et al 1976;Ryther 1954;Sameoto 1976;Sushchenya 1958;Taguchi and Ishi 1972. ) feeding rates may not be monotonic functions of temperature (Kersting and Van der Leeuw 1976;Zankai and Ponyi 1976), food concentration (Richman 1966;Rigler 197 1;Frost 1975;Mullin et al 1975;Muck and Lampert 1980;Downing 198 1;Porter et al 1982), or food particle volume (Allan et al 1977;McQueen 1970;Nival and Nival 1976).…”
Section: Methodsmentioning
confidence: 99%
“…5 to g), indicating that a constant proportion was removed per unit time, regardless of the feeding mode or particle size. The slope of the semi-log plot is the mean instantaneous feeding rate, g. The clearance rate (Strickler 1985) or the volume swept clear per unit time, F (Harvey 1937, Frost 1972, Durbin & Durbin 1975, may be determined from the relationship: the latter implies filtering activity. The clearance rate is an estimate of the volume from which all the food particles would have to be removed per unit time to produce the observed ingestion rates, I (Durbin & Durbin 1975, Marin et al 1986 …”
Section: Feeding Ratesmentioning
confidence: 99%